KOMPETENSI PEDAGOGIK MAHASISWA PROGRAM STUDI BIOLOGI UPH-TEACHERS COLLEGE PADA PPL-3 - Lastiar Roselyna Sitompul (Universitas Muhammadiyah Semarang, 2018)
One of UPH-Teachers College's graduate profiles is teacher with international standards. Thus, one of the competencies that a Christian teacher should have is a pedagogical competence. For this, UPH Teachers College is organizing an internship program for the teacher candidates in 747 th semester for 4 months in schools throughout Indonesia. It is expected that through this program, some recommendations related to pedagogical competencies will be made particular in Biology Department to equip the teachers candidates better in their pedagogical competences. The research method is quantitative descriptive. It aims for finding fact and describing factual condition. After analyzing the data descriptively, it was found that the pedagogic competence of teacher candidates in internship program based on the questionaire of teacher candidates showed that 3.77% categories as sufficient, 67.92% good, and 28.30% very good.According students perception from 9 schools of Lentera Harapan categorized them as very good, students from 7 Dian Harapan school categorizes them as good and students from 7 schools outside of the Pelita Harapan foundation categorizes them very good, and perception of mentor teachers categorized them as good.Keywords: Pedagogical competence, Internship program